The Relationship of Knowledge Levels About COVID-19 With COVID-19 Prevention Behavior In Oebobo Village Community Kupang - Vania Carla Devina; Herman Pieter Wungouw; Anita Lidesna Shinta Amat; Dominikus Minggu (Cendana Medical Journal, 2025)
Introduction: COVID-19 is a virus that can be transmitted from human to human (human to human transmission). This virus has spread widely in China and even to other countries. This virus can spread because of the travel history of people who have been infected with the corona virus. The increase in COVID-19 in Indonesia is also based on the lack of public knowledge about COVID-19. The existence of correct information can help people to increase their knowledge. Misinformation can make people's understanding also change. Therefore, the level of community knowledge greatly influences people's behavior. Behavior is an action that can also be interpreted as all activities carried out by someone which is the result of external stimuli that explain the knowledge they have. Community behavior in preventing COVID-19 can help reduce the increase in the incidence of COVID-19. Purpose: The purpose of this study was to determine the relationship between the level of knowledge about COVID-19 and COVID-19 prevention behavior in the community in Oebobo Village, Kupang. Methods: This type of research was an observational analytic using amethod cross sectional conducted on the people of Oebobo Village, Kupang City. . Data were obtained by filling out the Knowledge Questionnaire about COVID-19 and the COVID-19 Prevention Behavior Questionnaire by 100 respondents who met the inclusion criteria. Sampling was done by using purposive random sampling technique. The results were analyzed univariately and bivariately using thecorrelation test Spearman. Results: Data from 100 respondents showed, 64.0% had a good level of knowledge, 32.0% had a sufficient level of knowledge and 4.0% had a poor level of knowledge. For preventive behavior, 68.0% had good behavior, 32.0% had moderate behavior and none had bad behavior. The results of the bivariate analysis with the correlation test Spearman showed the results of p= 0.114 (p> 0.05) Conclusion: There is no significant relationship between the level of knowledge about COVID-19 and COVID-19 prevention behavior in the community in Oebobo Kupang Village